Expert Validation and Students’ Initial Field Trial Responses toward M-Write Academic Essay Writing Application - Wahyu Kyestiati Sumarno; Dwi Wahyuningtyas; Triubaida Maya Ardianti; Adinda Aulia Rahmawati; Putri Dian Shafira; Nur Imro’atus Solikha (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
Proficiency in English academic writing is still a problem for many students. However, there are no such digital learning media that facilitates academic writing practices. Considering these problems, this research tried to develop an M-Write application, a learning media that combine metacognitive and process-genre writing exercises. This study aims to determine the feasibility level of M-Write as a website-based academic essay writing application. The method used in testing the feasibility of this product includes the alpha test and beta test. The alpha test was carried out by three English Education experts; each of them assessed the aspects of the content, language use, and design. While the beta test was carried out by 25 students of the Computer Science Faculty, UPN “Veteran” Jawa Timur. The data collection technique was done by using a questionnaire and interview. Data analysis was carried out using quantitative descriptive techniques. The results of this study indicate that the M-Write application reached appropriate criteria in terms of content, language use, and design aspects. The percentages of each of these aspects are 71.9%, 73.3%, and 71.9%. While the results of the applications usage assessment by students also showed that the application was appropriate to be used with an average percentage of 75.9%.